Television Digital Broadcasting Migration 2022 Area Province Bengkulu - Yanto Yanto; Indria Indria (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
The enactment of the Employment Copyright Constitution automatically participates, including those related to broadcasting, like it or not, we have to be ready to welcome digitalization. For broadcasting industry players, migrating to digital TV is like leaving your own home. In this case, the government and the regional Indonesian broadcasting commission (KPID) can socialize and educate people who still lack knowledge, therefore the author wants to continue in scientific writing with the aim of this research aims to determine the migration of television digitization broadcasting 2022 in Bengkulu Province, this study uses descriptive qualitative method with interview, observation and documentation data collection tools. The results of the study show, in general, that local television has stated its readiness firmly, only there are still many obstacles and doubts regarding the technical way the broadcast will be carried out, in terms of regulation the KPID also still needs further information from the Ministry of Communication and Information regarding the use of the setting box and distribution system to society.